2020
DOI: 10.1111/trf.16020
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hematological malignancy in blood donors: A nationwide cohort study

Abstract: Background: There has been a concern that blood donations can increase the risk of hematological malignancies. We investigated if blood donations increase the risk of developing hematological malignancies, specifically acute lymphoblastic leukemia, acute myeloid leukemia (AML), chronic lymphocytic leukemia (CLL), chronic myeloid leukemia, Hodgkin lymphoma, and myeloma, as well other non-Hodgkin lymphoma. Study Design and Methods: In total, the study included 1,021,433 Swedish blood donors, with 19.5 million pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…In general, the observed association between blood donation and long‐term health outcomes across the studies were inconsistent. Several studies showed blood donation has a protective effect on CVD, cancer, and death, 5–7,10,11,13,19,21,23,29 while other studies showed blood donation had no association with CVD, cancer, and death 9,12,15,17,18,21,24,25,31 . Some studies also found that apheresis donation was associated with reduction in bone mineral density (BMD) and increased risk of fracture, 16,28 while other studies found no association between blood donation and BMD markers 22,26,27,30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the observed association between blood donation and long‐term health outcomes across the studies were inconsistent. Several studies showed blood donation has a protective effect on CVD, cancer, and death, 5–7,10,11,13,19,21,23,29 while other studies showed blood donation had no association with CVD, cancer, and death 9,12,15,17,18,21,24,25,31 . Some studies also found that apheresis donation was associated with reduction in bone mineral density (BMD) and increased risk of fracture, 16,28 while other studies found no association between blood donation and BMD markers 22,26,27,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed blood donation has a protective effect on CVD, cancer, and death, [5][6][7]10,11,13,19,21,23,29 while other studies showed blood donation had no association with CVD, cancer, and death. 9,12,15,17,18,21,24,25,31 Some studies also found that apheresis donation was associated with reduction in bone mineral density (BMD) and increased risk of fracture, 16,28 while other studies found no association between blood donation and BMD markers. 22,26,27,30 One of the studies reported that apheresis donors had an increased risk of bacterial infection.…”
Section: Main Outcomes Reported and Confounding Factors Consideredmentioning
confidence: 99%
“…Lastly, a Swedish case–control study identified a possible increased risk of non‐Hodgkin lymphoma in frequent plasma donors 18 . However, a subsequent national cohort study by the same group concluded that there was no convincing evidence of an increased risk of any hematological malignancy 19 …”
Section: Discussionmentioning
confidence: 99%
“…Through linkage with a range of nationwide health data registers, capturing data on all hospital‐based in‐ and outpatient care, as well as all causes of death, both donors and transfused patients can be followed for a range of health outcomes, irrespective of where and when they occurred. For details about the SCANDAT3‐S database, see previous publications 14,15 …”
Section: Methodsmentioning
confidence: 99%